An Analysis of Slang Words Used By Indonesian Young People - eda maaliah maaliah; aziz muhyiddin muhyiddin; yulius harry widodo (Universitas Katolik Widya Mandala Surabaya, 2022)
The aims of the study are: 1) to know whether there is a certain meaning of slang words used by young people. 2) to figure out the advantages will be gained from the analysis of the slang words used by Indonesian Young Peole by using the theory of dialectology and sociolinguistics. The objects or the data used in the study are slang words used by Indonesian Young People from some sources. This study was finished in State Polytechnic of Madiun. The method that is used in this research is qualitative descriptive. The data used in this research is slang words used by Indonesia People from some sources. The result of the research shown that some of slang words used by Indonesian Young People can be used to express a secret language, a f friendly language, an informal language, and for sexual languae. The young people as the user of it face the new experience with word creation, unconsciously they enrich the language.This research has so many list of datas related to slang words as the new vocabularies in their speech. It can be used to develop the method and the concept used in learning language, culture, and social life.